Clinicopathologic characteristics and prognostic impact of atypical EGFR mutations in completely resected lung adenocarcinoma. (December 2022) - She, Yunlang; Li, Shenghui; Deng, Jiajun; Ren, Yijiu; Zhao, Mengmeng; Zhong, Yifan; He, Yiming; Chen, Qiankun; Zhao, Deping; Zhu, Yuming; Hou, Likun; Wu, Chunyan; et al.
Abstract: Introduction: This study evaluated the clinicopathologic characteristics and prognostic impact of atypical epidermal growth factor receptor (EGFR) mutations in patients with completely resected lung adenocarcinoma (LUAD) and investigate whether adjuvant chemotherapy could benefit the survival outcomes for these subjects. Material and methods: We retrospectively reviewed resected LUAD samples from 8437 patients and identified 5358 EGFR-mutated (EGFRm) cases. Of these, 4847 had classical mutations, while 511 had atypical mutations. For further survival analysis, propensity score matching, Kaplan–Meier curve, and Cox regression analyses were conducted. Results: Of the 511 patients with atypical EGFRm LUAD, 131 patients had compound mutations. The frequency of exon 20 insertion (20-ins), G719X, L861Q, S768I, and de novo T790M were 30.3%, 32.7%, 21.9%, 9.2%, and 11.4%, respectively. These patients included a higher proportion of males than those with classical EGFRm LUAD. Between the 483 matched pairs of the classical and atypical EGFRm patients, no significant difference emerged in disease-free survival (DFS) ( p = 0.476). Patients with the L861Q mutation had the poorest DFS among those with atypical EGFRm LUAD ( p = 0.005). Cox regression analyses revealed that the L861Q mutation was an independent prognostic factor for DFS in 487 patients with solely atypical EGFRm LUAD. In addition, adjuvant chemotherapy did not improve the DFS for those patients, whether in stage IB ( p = 0.638) or II-III ( p = 0.505) of the disease. Conclusion: The L861Q mutation is an independent prognostic factor for DFS in patients with atypical EGFRm LUAD after complete resection who would not benefit from adjuvant chemotherapy regardless of disease stage. Graphical abstract: Image 1 Highlights: Resected atypical and classical EGFR-mutated lung adenocarcinoma have similar DFS. L861Q mutation is associated with the poorest DFS among atypical EGFR mutations. Adjuvant chemotherapy couldn't benefit atypical EGFR-mutated lung adenocarcinoma.